THE OPTIMIZATION OF CLASSROOM TRAINING OF ORTHODONTICS AT THE POSTGRADUATE LEVEL OF EDUCATION - S.P. Yarova; E.A. Kobtseva; E.S. Genzytskaya (Ukrainian Medical Stomatological Academy, 2015)
Orthodontics is a one of the complex sections of dentistry including for interns training. The study of orthodontics involves mastering a lot of information about the etiology, pathogenesis, clinic, diagnosis, treatment and prevention of dental-maxilla-facial anomalies. Memory is a process set of memorization, preservation, reproduction, remembering, and forgetting. According to the theory of forgetting by Ebbinghaus within the first hours a  person forgets to 60% of all captured information, and after six days in the memory is less than 20% of the total amount of original learned information. These data characterize a course of forgetting of logically unrelated, unthought information. Durability of memorization of meaningful material is considerably higher. Meaningful information is remembered in 9 times faster. One means of optimizing the interns learning of orthodontics in our department is use of the thematic crosswords. Crossword can be considered as a means of control of knowledge on practical training, as it reminds tests: the presence of questions that should be answered. The use of this type of study was perceived by interns willingly, since such a game form of learning activity is a common form of leisure. However, to solve a crossword interns need to study theoretical material by the use of textbooks, lectures, additional literature. This type of study work was successful form of thinking activation, cognitive and creative activity of the interns. It helped them in an interesting way to check and fix their knowledge on the subject, to develop horizons, increase motivation and interest in the study of orthodontics. It should be noted the organizational aspect of the question when using the crosswords in the practical classes. In our view, there are the following options of organization of interns work: individual self-study with crosswords (simultaneously of the whole group or part of them) and the decision of the same crossword by two teams of group on getting the best since the end of one of the teams. Each of these options has their own advantages. In the first case, interns have favorable conditions for the individualization of their studying. The effectiveness of the second option of their work with crosswords can be explained by its group principle, which is one of the factors of intensification of training. At carrying out of classes we considered the possibility of self-making of crossword by interns. However, our experience has shown that this form of creative work takes a lot of time in class. This is a good method of interns' interactive training, but more efficiently it can be used for extracurricular training. Thus, long-term use of crosswords as an interactive form of training or control of the interns' knowledge during practical classes enables us to identify the following advantages of this method: increasing of interest, independence, interns' creativity in the assimilation of knowledge; formation of skills in the practical application; the increase in the active vocabulary of special terms, and others. Finally all of this can intensify of educational process and achieve of higher quality assimilation of the material for orthodontics.